Rehabilitation in patients with lymphoma: An overview of Systematic Reviews - Bhasker Amatya; Fary Khan; Thomas E. Lew; Michael Dickinson (Medical Journals Sweden, 2021)
Objective: To evaluate existing evidence from published systematic reviews for the effectiveness of rehabilitation interventions in patients with lymphoma. Data sources: A comprehensive literature search was conducted using medical/health science databases up to 1 October 2020. Bibliographies of pertinent articles, journals and grey literature were searched. Data extraction and synthesis: Two reviewers independently selected and reviewed potential reviews for methodological quality and graded the quality of evidence for outcomes using validated tools. Any discrepancies were resolved by final group consensus. Results: Twelve systematic reviews (n = 101 studies, 87,132 patients with lymphoma) evaluated 3 broad categories of rehabilitation interventions (physical modalities, nutrition and complementary medicine). Most reviews were of moderate-to-low methodological quality. The findings suggest: moderate-quality evidence for exercise programmes for improved fatigue and sleep disturbance; low-quality evidence for exercise therapy alone and qigong/tai chi for improved symptoms and overall quality of life, and an inverse association between sunlight/ultraviolet radiation exposure and incidence of non-Hodgkin's lymphoma; and very low-quality evidence for beneficial effects of yoga for sleep disturbances. Association between physical activity and lymphoma risk is indistinct. Conclusion: Despite a range of rehabilitation modalities used for patients with lymphoma, high-quality evidence for many is sparse. Beneficial effects of exercise programmes were noted for fatigue, psychological symptoms and quality of life. More research with robust study design is required to determine the effective rehabilitation approaches.